Business strategies and ethical challenges in the digital ecosystem - Tabaghdehi, S. Asieh H.; Foroundi, Pantea (Emerald Publishing Limited, 2024)
The emergence of new digital technologies, awareness of corporate social responsibility, and the greater need for innovation and problem-solving skills are becoming a de-facto part of the everyday management agenda. A key question to be answered in these turbulent times is, how is it possible for corporations to incorporate safety, security, and satisfaction of stakeholders in the design of their business models while they are struggling to achieve sustainability goals related to the environment and climate change? The chapters in Business Strategies and Ethical Challenges in the Digital Ecosystem act as a forum for examining current and future trends related to management and technological adoption. The research encourages academics and practitioners to use a multi-disciplinary approach to boldly bring together bodies of related knowledge to produce new insights exploring digital business strategy and industry 5.0, changing consumer behaviour, sustainability, marketing, ethics, data security and much more. The findings are relevant and useful for academics, researchers, policy makers and management executives.